Financial sector regulation reforms in South Africa: Post-adoption review of Socio-Economic Impact Assessment System that justified the Twin Peaks Regulatory model - Edward W. Khumalo; Jan van Romburgh; Jacqui-Lyn McIntyre (Africa’s Public Service Delivery & Performance Review, 2026)
Background: The Twin Peaks Regulatory (TPR) model was adopted by the government to serve as a prudential and market conduct oversight tool for South Africa’s financial sector. Since its implementation, the country has faced challenges in inadequate social cohesion, financial security and inclusion, economic growth and development. Aim: To assess the validity of the Socio-Economic Impact Assessment System’s (SEIAS) findings and the tool that rationalised regulatory reforms within the financial sector in South Africa. Setting: The SEIAS findings on the financial sector were used to gain insights into socio-economic impacts in South Africa before regulatory transformation. Methods: This study used a qualitative research method and adopted a desktop approach to collect secondary data to assess the validity of the Social economic Impact Assessment (SEIA) studies and tool that supported the adoption of the TPR model for the financial sector. Results: The study revealed that despite a positive SEIAS outcome, which led to the promulgation of the Financial Sector Regulation (FSR) Act of 2017 and the adoption of the TPR model in the financial sector, the reforms have not made a meaningful contribution to alleviating the challenges related to social cohesion, financial security and economic growth in South Africa. Conclusion: The SEIAS model alone is not sufficient to accurately capture the socio-economic challenges required to support credible policy reforms, as it lacks the depth and analytical accuracy that is needed for socio-economic measurement. The model has failed to accurately predict the impact of financial reforms and the TPR model in South Africa. Contribution: The findings of this study highlighted the weaknesses of SEIA studies. Although mandatory, this tool alone is not sufficient to predict the socio-economic impact of proposed legislation, policies and regulatory reforms.